2015
DOI: 10.1063/1.4918628
|View full text |Cite
|
Sign up to set email alerts
|

Scaling temperature dependent rheology of magnetorheological fluids

Abstract: Articles you may be interested inRheological characterization of a magnetorheological ferrofluid using iron nitride nanoparticles Magnetorheological behavior of magnetite covered clay particles in aqueous suspensions J. Appl. Phys. 112, 043917 (2012); 10.1063/1.4748878Magnetorheology and sedimentation behavior of an aqueous suspension of surface modified carbonyl iron particles Magnetorheological (MR) fluids are suspensions of micron-scale magnetizable particles suspended in a carrier fluid. When field is appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 8 publications
0
16
0
1
Order By: Relevance
“…In particular, both thermal and electric conductivities increase when the MRF is magnetized in the field direction. Some recent examples on thermal studies are as follows: Ocalan and McKinley, 148 Yildirim and Genç, 169 Sherman et al 170 and Patel and Upadhyay. 171 Very recently, Ruan et al 172 investigated the influence of oscillatory shear on the magnetic field dependent electric conductivity of MRFs.…”
Section: Review Soft Mattermentioning
confidence: 99%
“…In particular, both thermal and electric conductivities increase when the MRF is magnetized in the field direction. Some recent examples on thermal studies are as follows: Ocalan and McKinley, 148 Yildirim and Genç, 169 Sherman et al 170 and Patel and Upadhyay. 171 Very recently, Ruan et al 172 investigated the influence of oscillatory shear on the magnetic field dependent electric conductivity of MRFs.…”
Section: Review Soft Mattermentioning
confidence: 99%
“…4 the opposite happens. Hence, the only plausible conclusion is the relationship between current and voltage, in our scenario, is not constant as in (2). Therefore, given any constant value for the current amplitude (different from zero), the relationship between MR fluid's temperature and coil's resistance is well defined.…”
Section: Preliminary Data Analysismentioning
confidence: 80%
“…It is well known in literature that the viscosity of the MR fluid is significantly affected by the operating temperature [2], [3], [4] diminishing the damping capabilities of the MR damper [5], [6]. As remarked in [7], since the MR damper dissipates the vehicle mechanical energy, the heating of the internal damper fluid cannot be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…The authors attribute the difference in behavior to the viscosity decrease of the carrier fluid dominating in the absence of magnetic field, whereas magnetic attraction between iron particles is dominant in the presence of magnetic field. Computational work by Sherman et al [ 67 ] similarly showed that temperature behavior is dependent on the carrier fluid for CI‐based polyalphaolephin (PAO) hydrocarbon oil MRFs. Wu et al [ 68 ] investigated the effect of particle size and concentration in addition to temperature on τ y and magnetization.…”
Section: Ci‐based Mrfsmentioning
confidence: 99%